Analisis Partisipasi Masyarakat Terhadap Pengembangan Desa Wisata “Bukit Sebrang” Desa Sidoharjo Kecamatan Jambon Kabupaten Ponorogo - Yusuf Adam Hilman; Samsul Arifin (Jurnal Ilmu Politik dan Pemerintahan, 2020)
Tourism in rural development in various regions since the last few years has used tourism as a means of empowering the community and making tourism a leading sector. This study uses a description method to describe a verbal description about the management of natural tourism in the village of Sidoharjo, Jambon subdistrict, Ponorogo regency on tourist attractions because the uniqueness and beauty of the tour is used as a means of community empowerment to explore the economy in the tourist surroundings. In its management it must involve the community starting from management planning. With the responsibility of the community towards the potential of tourism objects, the community must be involved in management, implementation and evaluation will encourage a sense of belonging to the potential and tourism objects that guarantee the preservation of the potential and the object.